(untitled) (Bangladesh Journal of Botany, 2025)
The growth and development of pineapple plants and it’s response to different flower induction chemicals inside polyhouse microclimatic conditions were studied in hot-humid coastal conditions during 2017-18 at ICAR-CCARI, Goa. The existing naturally ventilated double-span polyhouse was structurally modified to accommodate heavy rainfall, and the additional space created on both sides was utilized to grow pineapple plants with fertigation and flower induction treatment. The day temperature (37.00-42.50ºC) and night temperature (12.16-22.87ºC) inside the polyhouse were higher than the ambient conditions throughout the growing period of the crop (31.94-34.16ºC and 19.65-24.46ºC, respectively). The relative humidity inside the polyhouse ranged from 50.75-97.85%, whereas in ambient conditions, it was 37.75-91.90%. Among the different flower induction treatments, the ethephon 25 ppm+urea 2% + sodium carbonate 0.04% treatment was the most effective with the earliest flowering (33.33 days), which was 15.11 days ahead of the control (48.44 days). Pineapple can be successfully grown inside an existing polyhouse to utilize the additional spaces with fertigation and flower induction with a 50 ml solution of ethephon 25 ppm + urea 2% + sodium carbonate 0.04% with a B: C ratio of 1.15. Bangladesh J. Bot. 54(2): 293-300, 2025 (June)